The abrasive wear behavior of Al2014 composites reinforced with Ti5Si3-coated SiCP. (August 2017) - Yang, Delong; Qiu, Feng; Zhao, Qinglong; Wang, Lei; Jiang, Qichuan
Abstract: This work described the differences of abrasive wear behavior and wear mechanism between 5 and 20 vol% salt-bath plated Ti5 Si3 -coated and uncoated SiCP /Al2014 composites. The composites were prepared by the semisolid sintering, and the wear experiment was conducted on a pin-on-disk tester under 5–20 N. The results suggested that Ti5 Si3 -coated SiCP /Al2014 composites exhibited better abrasion resistance than uncoated ones when tested under same condition. The enhanced abrasive wear resistance was benefited from the improved interfacial combination between Ti5 Si3 -coated SiCP and Al2014, which could prevent the SiCP from "being pulled out" and abrasive particle penetrating deeply into matrix. Besides, lower porosity and higher hardness also contributed to part of enhanced wear resistance for Ti5 Si3 -coated SiCP /Al2014 composites. Highlights: The abrasive wear behavior of Ti5Si3-coated SiCP/Al2014 has been firstly investigated. Ti5Si3-coated SiCP/Al2014 showed better abrasive wear resistance than uncoated one. The better wear resistance was mainly attributed to the enhanced interfacial bonding.